Perencanaan Laba Menggunakan Analisis Cost-Volume-Profit pada Usaha Amora Food - Lydia Mayendra; Ulfi Maryati; Rini Susanti; Alyani Atsarina (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This study analyzes profit planning at Amora Food using the Cost–Volume–Profit (CVP) method as a managerial tool for short-term decision-making. The company’s main challenge lies in its lack of cost classification between fixed and variable components and the absence of a systematic profit-planning mechanism, which hinders the determination of accurate sales targets. The research employed interviews, direct observation, and documentation of production processes and financial data. The analysis included cost classification, calculation of contribution margin ratios, break-even points, profit targets, and sensitivity to changes in CVP assumptions.The findings show that Sambalado Tanak has the highest contribution margin (74%), while Rendang has the lowest (18%). To achieve a targeted profit of Rp 80,000,000 for the January–March 2025 period, the company must sell 1,773 packs of Rendang, 3,325 packs of Kerupuk Jangek Serundeng, 997 packs of Kerupuk Opak Balado, 2,571 packs of Teri Kacang Balado, and 1,330 bottles of Sambalado Tanak.